Novel method for measuring diffusion coefficient of substance in inclusions in steel
Through high-temperature confocal equipment, simulated the liquid steel-inclusion reaction experiment, combined with scanning electron microscopy, the problem of difficult monitoring of changes in alumina inclusion composition in steel is solved, and effective control of steel performance is achieved.
Patent Information
- Application Number
- CN202411924582.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-25
AI Technical Summary
The prior art is difficult to accurately monitor and control the composition changes of alumina inclusions in steel, especially during calcium treatment, which leads to the impact of steel properties.
The liquid steel-inclusion reaction experiment was simulated by high-temperature confocal equipment, and the inclusion components at different moments were analyzed in combination with scanning electron microscopy, the initial conditions required for the kinetic model were collected, and the mass transfer coefficient of the substance in the inclusion was estimated.
Accurate analysis and prediction of the changes in inclusion components in steel is achieved, effective experimental and production guidance is provided, and the control ability of steel performance is improved.
Smart Images

Figure CN119757130A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metallurgy, and in particular relates to a new method for measuring the diffusion coefficient of inclusions of a substance in steel. Background Art
[0002] With the increasing demand for high-quality steel from users, the control of non-metallic inclusions in steel has become particularly important. In order to achieve high cleanliness of steel, the inclusions in steel must be accurately monitored and controlled. For killed steel, alumina inclusions are the most important inclusions, which have high melting point and high hardness. A large number of alumina inclusions in the steel matrix will cause stress concentration, seriously affecting the plasticity, toughness and fatigue resistance of the steel. At the same time, a large number of alumina inclusions will be deposited inside the submerged nozzle, causing nozzle nodules and blockages, seriously affecting the smooth operation of the continuous casting process. At present, the calcium treatment process is the most commonly used way to solve the alumina inclusions in steel. Calcium treatment can modify alumina inclusions into spherical calcium aluminate inclusions with a lower melting point, which are easy to remove from the molten steel. Even if there is still a small amount of residue, its harm to the performance of the steel is less than that of solid alumina inclusions.
[0003] In recent years, in order to effectively control the composition of alumina inclusions in steel, metallurgists have developed different kinetic models to better predict the shape, size, quantity and distribution of inclusions during the modification process. The commonly used model is the multi-layer unreacted core model, which considers the influence of a substance in the diffusion process. At the same time, in the process of establishing the kinetic model, the inclusions in the steel are usually assumed to be spherical for the convenience of calculation. However, in actual production, inclusions usually exist in the molten steel in irregular shapes, which leads to some controversy over the kinetic parameters and other calculation results proposed based on this assumption.
[0004] At present, high temperature confocal microscopy is a new research method in the field of iron and steel metallurgy. A large number of scholars use high temperature confocal microscopy equipment to study the collision behavior of inclusions in steel and the dissolution behavior of inclusions in slag. However, due to the limitations of the experimental method of high temperature confocal microscopy, there are few studies on the modification behavior of inclusions. The predecessors mainly observed the modification process of endogenous alumina inclusions in steel into spherical calcium aluminate inclusions in situ through high temperature confocal microscopy, and did not analyze the composition of the target inclusions at different times. This is because the experimental method has some shortcomings: (1) Since the number of endogenous alumina inclusions on the surface of molten steel is large and collisions occur, it makes it particularly difficult to track and observe the modification process of the target inclusions in steel; (2) The accuracy of the starting point of the modification time of alumina inclusions in steel cannot be guaranteed; (3) The operation process is complicated and difficult to control. In order to meet the need to predict the composition change of calcium-treated alumina inclusions, the present invention provides a new method for measuring the diffusion coefficient of a substance in steel inclusions. Summary of the invention
[0005] In order to solve the above technical problems, the present invention proposes a new method for measuring the diffusion coefficient of a substance in inclusions in steel to solve the above problems existing in the prior art.
[0006] To achieve the above object, the present invention provides a new method for measuring the diffusion coefficient of a substance in inclusions in steel, comprising:
[0007] Acquiring experimental materials and pre-treating the experimental materials; wherein the experimental materials include steel samples and inclusions;
[0008] The high-temperature modification experiment was carried out on the pre-treated experimental materials through high-temperature confocal equipment, and the inclusion composition at different times was analyzed according to the experimental data;
[0009] The initial conditions of the kinetic model are obtained, and the mass transfer coefficient of inclusions is estimated based on the initial conditions and inclusion composition analysis.
[0010] Optionally, the process of pretreating the steel sample includes:
[0011] After cutting the steel sample into several cylinders of the same preset size, the steel sample is cold mounted using UV glue; the prepared steel sample is polished and cleaned step by step; after polishing, it is placed in a container filled with alcohol for ultrasonic cleaning.
[0012] Optionally, the preset dimensions include height and diameter, the height ranges from 3-5 mm, and the diameter ranges from 5-10 mm.
[0013] Optionally, the process of pre-treating the inclusions includes:
[0014] Slag containing the ingredients required for the experiment is obtained and ground and mixed to obtain powdered preheated slag; the powdered preheated slag is pressed into round cakes of a preset size, the round cakes are heated to prepare pre-melted slag, the pre-melted slag is crushed and selected, and inclusion particles that meet size conditions are screened out; wherein the preset size conditions include the size and the error of each group of inclusion particles, the size is 100-300μm, and the error between the sizes of each group of inclusion particles does not exceed 40μm.
[0015] Optionally, when the temperature is raised to prepare the pre-melted slag, the insulation temperature needs to be controlled to be 50-100° C. higher than the complete melting temperature of the slag, and the insulation time needs to be controlled to be 20-30 minutes.
[0016] Optionally, a high temperature modification experiment is performed on the pretreated experimental material by a high temperature confocal device, and the process of analyzing the inclusion composition at different times according to the experimental data includes:
[0017] The reaction time corresponding to each group of inclusion particles is obtained through preliminary experiments, and a high-temperature modification experiment is carried out on the pretreated experimental material based on the reaction time; when the reaction time is reached, helium is filled into the heating furnace for cooling; the experimental material after the experiment is taken out, and the composition of the inclusion particles is analyzed using a scanning electron microscope to obtain the inclusion composition; wherein the cooling rate is controlled at 300-1000°C.
[0018] Optionally, the initial conditions of the kinetic model include the density and volume of the inclusion particles; wherein the density of the inclusion particles is calculated based on the relationship between the oxide molar volume and temperature and the following formula:
[0019] ρ liquidslag =∑x MO ·ρ MO ;
[0020]
[0021] In the formula, ρ liquid slag is the density of liquid slag, kg·m -3 ;x MO is the mass percentage of different oxides in the slag, wt%; ρ MO is the density of different oxides in the slag, kg·m -3 ;M MO is the molar mass of different oxides in the slag, kg·mol -1 ; Z MO is the molar volume of different oxides in the slag, m 3 ·mol -1 .
[0022] Optionally, the volume of inclusion particles is calculated as follows:
[0023]
[0024] V is the volume of the liquid inclusion particle, m -3 ; R is the radius of the liquid inclusion particles after being flattened on the surface of the steel sample, m; θ is the contact angle between the liquid inclusion particles and the solid steel.
[0025] Compared with the prior art, the present invention has the following advantages and technical effects:
[0026] The invention discloses a new method for measuring the diffusion coefficient of a substance in inclusions in steel. First, in the preparation of experimental materials, the experimental materials include steel samples and inclusions, wherein the steel samples need to be cut into columns with a certain size, and the inclusion particles need to use high-temperature equipment to heat a certain ratio of slag to prepare pre-melted slag, and the pre-melted slag is crushed and selected to select inclusion particles of suitable size; then a high-temperature laser confocal device is used to perform a high-temperature modification experiment on the prepared experimental sample, and an electron microscope device is used to analyze the inclusion components at different times; finally, the initial conditions required for the kinetic model are collected, and the mass transfer coefficient of the substance in the inclusion is estimated. The invention uses a high-temperature confocal device to simulate a molten steel-inclusion reaction experiment, combines an electron microscope to analyze the components of the inclusions at different times, collects the parameters required by the model, and finally estimates the mass transfer coefficient of the substance in the inclusion. The calculation results are similar to the results of predecessors, proving the feasibility of the experiment. The method provided by the invention has an important experimental and production guiding role and a good application and promotion prospect. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0028] Figure 1 A schematic diagram of steel sample preparation and chemical analysis according to an embodiment of the present invention;
[0029] Figure 2 Schematic diagram of the preparation process of inclusion particles according to an embodiment of the present invention;
[0030] Figure 3 This is a schematic diagram of the whole process of changes of inclusion particles on the steel surface according to an embodiment of the present invention;
[0031] Figure 4 A schematic diagram of changes in the composition of inclusion particles over time according to an embodiment of the present invention;
[0032] Figure 5 It is a schematic diagram of the projection of the liquid inclusion on the solid steel surface and its shape on the solid surface according to an embodiment of the present invention;
[0033] Figure 6 The steel in the embodiment of the present invention Schematic diagram of the relationship between and reaction time;
[0034] Figure 7 The steel in the embodiment of the present invention Schematic diagram of the relationship between and reaction time;
[0035] Figure 8Schematic diagrams of the effect of steels with different aluminum contents on the evolution of inclusion particle composition according to an embodiment of the present invention, (a) is a schematic diagram when T.Al=145ppm, (b) is a schematic diagram when T.Al=280ppm, and (c) is a schematic diagram when T.Al=420ppm;
[0036] Fig. 9 The logarithmic values of the changes in the contents of Al2O3 and SiO2 in the steel with T.Al=145ppm according to the embodiment of the present invention change over time; (a) is the change in Al2O3, and (b) is the change in SiO2;
[0037] Fig.10 The logarithmic values of the changes in the contents of Al2O3 and SiO2 in the steel with T.Al=280ppm according to the embodiment of the present invention change over time; (a) is the change in Al2O3, and (b) is the change in SiO2;
[0038] Fig.11 The logarithmic values of the changes in the contents of Al2O3 and SiO2 in the steel with T.Al=420ppm according to the embodiment of the present invention change over time; (a) is the change in Al2O3, and (b) is the change in SiO2;
[0039] Fig.12 The figure is a schematic diagram of a method flow of an embodiment of the present invention. DETAILED DESCRIPTION
[0040] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present application will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0041] It should be noted that the steps shown in the flowcharts of the accompanying drawings can be executed in a computer system such as a set of computer executable instructions, and that, although a logical order is shown in the flowcharts, in some cases, the steps shown or described can be executed in an order different from that shown here.
[0042] Embodiment 1
[0043] like Fig.12 As shown, this embodiment provides a new method for measuring the diffusion coefficient of a substance in inclusions in steel. Taking the measurement of the mass transfer coefficient of CaO in CaO-Al2O3-MgO-SiO2 inclusion particles as an example, the specific operation steps are as follows:
[0044] S1: In the preparation of experimental materials, the experimental materials include steel samples and inclusions. The steel samples need to be cut into columns with a certain size. The inclusion particles need to use high-temperature equipment to heat up the slag of a certain ratio to prepare pre-melted slag, and the pre-melted slag is crushed and selected to select inclusion particles of appropriate size.
[0045] S2: Use high-temperature laser confocal equipment to carry out high-temperature modification experiments, and use electron microscope equipment to analyze the composition of inclusions at different times;
[0046] S3: Collect the initial conditions required for the kinetic model and estimate the mass transfer coefficient of the species in the inclusion.
[0047] As a preferred embodiment, the steel sample in step S1 is industrial Al deoxidized steel, and its specific composition is shown in Table 1. The Al deoxidized steel is cut into several cylinders with a diameter of 5 mm and a height of 3 mm. In order to ensure a clear imaging effect when observing the steel sample under a high-temperature laser confocal microscope, the upper and lower bottom surfaces of the sample must be kept strictly parallel. The steel sample is cold mounted using UV glue, and then the steel sample is polished step by step using different types of sandpaper (300#, 600#, 800#, 1200#, 2400#), and then cleaned with alcohol, and then polished with 8μm and 1μm polishing liquid. Finally, the polished steel sample is placed in a beaker filled with alcohol, and the beaker is placed in an ultrasonic cleaner for cleaning for 5 minutes to thoroughly remove impurities and contaminants remaining on the surface. The steel sample preparation and chemical analysis scheme are as follows. Figure 1 shown.
[0048] Table 1
[0049]
[0050] As a preferred embodiment, the main components of the inclusion particles in step S1 are CaO, Al2O3, MgO and SiO2. First, CaO (Chinese medicine, purity ≥98%), Al2O3 (Chinese medicine, purity ≥99%), SiO2 (Chinese medicine, purity ≥99%) and MgO (Chinese medicine, purity ≥99%) reagents are used in a certain proportion to prepare slag of the required composition for the experiment, which is placed in a quartz grinding crucible for grinding, mixing and other operations to ensure that the preheated slag composition is uniform; then, the powder sample is placed in a specific tableting mold, and then appropriate pressure is applied to compress the powder into a diameter of 10 mm. The crucible is 3 mm high and has a round cake shape. Finally, the platinum crucible is placed in the heating furnace chamber of a high-temperature confocal microscope (CSLM). It is melted at 1600°C in the heating furnace of the CSLM and kept warm for 20 minutes to achieve a uniform slag composition. Then, He gas is used to rapidly cool at 1200°C per minute to obtain the slag sample required for the experiment to prevent the crystallization of the slag sample from affecting the subsequent inclusion particles. The initial composition is close to the slag composition of the ratio before the experiment. The inclusion particles are analyzed by XRF, and the contents of CaO, Al2O3, MgO and SiO2 are 55.50%, 29.77%, 7.98% and 6.75%, respectively. Finally, the platinum crucible is taken out, and the pre-melted slag in the platinum crucible is crushed with pointed stainless steel tweezers, and particles of suitable size are selected from it as inclusion particles for subsequent CSLM experiments. The specific operation method is as follows: Figure 2 shown.
[0051] As a preferred embodiment, in the high temperature modification experiment in step S2, as the temperature rises to 1732.4K, the inclusion particles begin to melt, and their irregular edges gradually become smooth. When the temperature continues to rise to 1786.6K, the inclusion particles further melt, and their shape changes to spherical. When the temperature reaches 1857.1K, the steel surface placed under the slag begins to melt, and the slag begins to float on the surface of the molten steel. This moment is the start time of the reaction between the inclusions and the molten steel. Then the temperature is controlled and the reaction time is recorded. The whole process of the change of the inclusion particles on the steel surface is as follows: Figure 3 As shown. In order to prevent the inclusion particles from moving too fast and leaving the observation range, the argon flow rate needs to be reduced during the experiment to avoid violent fluctuations on the surface of the molten steel. When the reaction time reaches the target duration, the cooling procedure begins by filling the heating furnace with He gas to achieve rapid cooling. The steel sample is then taken out and a scanning electron microscope is used to analyze the composition of the inclusion particles. During the entire transfer process, the steel sample can be placed in an alcohol bottle to prevent its surface from being contaminated. During the entire high-temperature confocal experiment, the high-temperature confocal microscope and the scanning electron microscope need to work repeatedly in sequence. Only the reaction time between the inclusions and the molten steel needs to be changed. Figure 4 is the change of inclusion particle composition over time.
[0052] Furthermore, the initial conditions of the kinetic model include the density and volume of the inclusion particles; wherein the density of the inclusion particles is calculated based on the relationship between the oxide molar volume and temperature and the following formula:
[0053] ρ liquid slag =∑x MO ·ρ MO (1)
[0054]
[0055] In the formula, ρ liquid slag is the density of liquid slag, kg·m -3 ;x MO is the mass percentage of different oxides in the slag, wt%; ρ MO is the density of different oxides in the slag, kg·m -3 ;M MO is the molar mass of different oxides in the slag, kg·mol -1 ; Z MO is the molar volume of different oxides in the slag, m 3 ·mol -1 .
[0056] Furthermore, the volume calculation formula of inclusion particles is as follows:
[0057]
[0058] V is the volume of the liquid inclusion particle, m -3 ; R is the radius of the liquid inclusion particles after being flattened on the surface of the steel sample, m; θ is the contact angle between the liquid inclusion particles and the solid steel.
[0059] As a preferred embodiment, the volume calculation of the inclusion particles in the initial condition of the kinetic model in step S2 is based on the literature search. The contact angle between the liquid inclusion particles and the solid steel is 83.18°. Using formula (3), the volume of the liquid inclusion particles is 1.87×10 -11 m 3 . Figure 5 It is the projection of liquid inclusions on the solid steel surface and its shape on the solid surface.
[0060] As a preferred embodiment, the density of inclusion particles in the initial condition of the kinetic model in step S2 is calculated by substituting the composition of inclusion particles measured by XRF into formulas (1) to (2). The density of liquid inclusion particles is calculated to be 2891 kg·m -3 .
[0061] Specifically, the relationship between the oxide molar volume and the temperature T is shown in Table 2.
[0062] Table 2
[0063]
[0064] As a preferred embodiment, in step S3, the mass transfer coefficient of the substance in the inclusion is estimated. Based on the unreacted core model, since the [Al] content in the molten steel is relatively high, the boundary layer diffusion of [Al] on the molten steel side of the inclusion will not become a limiting link. At the same time, the chemical reaction on the interface is usually fast, so the limiting link of the reaction process may be the mass transfer of CaO or Al2O3 in the inclusion particles. Assuming that the rate-controlling link of the reaction is the diffusion of CaO inside the inclusion, its mass transfer rate is:
[0065]
[0066] Among them, (%CaO) inc is the mass fraction of CaO in inclusions at different times; is the mass fraction of CaO on the molten steel-inclusion interface; A is the contact area between inclusions and molten steel, m 2 ; V is the volume of the inclusion, m 3 ;k CaO is the diffusion coefficient of CaO in inclusions, m / s. Integrating formula 4 yields:
[0067]
[0068] Substitute the experimental results into formula 6 and perform linear fitting. Similarly, fit the diffusion coefficient of Al2O3 in inclusions. The fitting results of the diffusion coefficients of CaO and Al2O3 in inclusions are as follows: Figure 6 and Figure 7 As shown in the figure, it is found that the logarithmic value of the change of CaO content in inclusions is linearly related to the reaction time, indicating that the limiting factor of inclusions is the diffusion coefficient of CaO in inclusions. The calculated diffusion coefficient is about 3.77×10 -6 m·s -1 .
[0069] Embodiment 2
[0070] The technical solution proposed by the present invention is: a method for measuring the diffusion coefficient of a substance in inclusions in steel. Taking the measurement of the mass transfer coefficient of SiO2 in CaO-Al2O3-MgO-SiO2 inclusion particles as an example, the specific operation steps are as follows:
[0071] S1: In the preparation of experimental materials, the experimental materials include steel samples and inclusions. The steel samples need to be cut into columns with a certain size. The inclusion particles need to use high-temperature equipment to heat up the slag of a certain ratio to prepare pre-melted slag, and the pre-melted slag is crushed and selected to select inclusion particles of appropriate size.
[0072] S2: Use high-temperature laser confocal equipment to carry out high-temperature modification experiments, and use electron microscope equipment to analyze the composition of inclusions at different times;
[0073] S3: Collect the initial conditions required for the kinetic model and estimate the mass transfer coefficient of the species in the inclusion.
[0074] Preferably, the steel sample in step S1 is Al deoxidized steel smelted in the laboratory, and its specific composition is shown in Table 3. Al deoxidized steel with different contents is cut into several cylinders with a diameter of 5 mm and a height of 3 mm. In order to ensure a clear imaging effect when observing the steel sample under a high-temperature laser confocal microscope, the upper and lower bottom surfaces of the sample must be kept strictly parallel. The steel sample is cold mounted using UV glue, and the steel sample is polished step by step using different types of sandpaper (300#, 600#, 800#, 1200#, 2400#), then cleaned with alcohol, and then polished with 8μm and 1μm polishing liquid. Finally, the polished steel sample is placed in a beaker filled with alcohol, and the beaker is placed in an ultrasonic cleaner for cleaning for 5 minutes to completely remove impurities and contaminants remaining on the surface.
[0075] Table 3
[0076]
[0077] Preferably, the main components of the inclusion particles in step S1 are CaO, Al2O3, and SiO2. First, CaO (Chinese medicine, purity ≥ 98%), Al2O3 (Chinese medicine, purity ≥ 99%), and SiO2 (Chinese medicine, purity ≥ 99%) reagents are used in a certain proportion to prepare slag of the required components for the experiment, which is placed in a quartz grinding crucible for grinding, mixing, and other operations to ensure that the preheated slag has a uniform composition; then, the powder sample is placed in a specific tableting mold, and then appropriate pressure is applied to compress the powder into a round cake with a diameter of 10 mm and a height of 3 mm. shape; finally, the platinum crucible was placed in the heating furnace chamber of a high-temperature confocal microscope (CSLM), melted at 1600°C in the heating furnace of the CSLM and kept warm for 20 minutes to achieve the purpose of uniform slag composition, and then He gas was used to quench at 1200°C per minute to obtain the slag sample required for the experiment to prevent the slag sample crystallization from affecting the initial composition of the subsequent inclusion particles. The composition was close to the slag composition of the ratio before the experiment, and the inclusion particles were analyzed by XRF, where the contents of CaO, Al2O3 and SiO2 were 17.02%, 39.22% and 43.75%, respectively. Finally, the platinum crucible was taken out, and the pre-melted slag in the platinum crucible was crushed with pointed stainless steel tweezers, and particles of suitable size were selected from it as inclusion particles for subsequent CSLM experiments.
[0078] Preferably, the high temperature modification experiment in step S2 is conducted on steels with different aluminum contents and inclusion particles of a certain size. Figure 8 Effect of steels with different aluminum contents on the evolution of inclusion particle composition.
[0079] Preferably, the volume calculation of the inclusion particles under the initial condition in the kinetic model in step S2 is based on the literature search. The contact angle between the liquid inclusion particles and the solid steel is 36°. Using formula 3, the volumes of the three groups of liquid inclusion particles are 6.64×10 -13 m 3 , 6.60×10 -13 m 3 and 6.31×10 -13 m 3 .
[0080] Preferably, in the calculation of the density of inclusion particles under the initial conditions in the kinetic model in step S2, the composition of the inclusion particles measured by XRF is substituted into formulas (1) to (2). After calculation, the density of the liquid inclusion particles is 2817.4 kg·m -3 .
[0081] Preferably, in step S3, the mass transfer coefficient of the substance in the inclusion is estimated. Based on the unreacted core model, since the [Al] content in the molten steel is relatively high, the boundary layer diffusion of [Al] on the molten steel side of the inclusion will not become a limiting link. At the same time, the chemical reaction on the interface is usually fast, so the limiting link of the reaction process may be the mass transfer of SiO2 or Al2O3 in the inclusion particles. Assuming that the rate-controlling link of the reaction is the diffusion of SiO2 inside the inclusion, its mass transfer rate is:
[0082]
[0083] Among them, (%SiO2) inc is the mass fraction of SiO2 in inclusions at different times t; is the mass fraction of SiO2 on the molten steel-inclusion interface; A is the contact area between inclusions and molten steel, m 2 ; V is the volume of the inclusion, m 3 ; is the diffusion coefficient of SiO2 in inclusions, m / s. Integrating formula 7 yields:
[0084]
[0085] Substitute the experimental results into formula 9 and perform linear fitting. Similarly, fit the diffusion coefficient of Al2O3 in inclusions. The fitting results of the diffusion coefficients of SiO2 and Al2O3 in inclusions are as follows: Fig. 9 , Fig.10 and Fig.11 As shown in the figure, the experiment found that the logarithmic value of the change of SiO2 content in inclusions in different groups of experiments was linearly related to the reaction time, indicating that the limiting factor of inclusions is the diffusion coefficient of SiO2 in inclusions. The calculated diffusion coefficients are 6.38×10 -8 m·s -1 ,7.13×10 -8 m·s -1 and 8.38×10 -8 m·s -1 The results are quite different from the values in the literature of previous studies. Since the reaction of Al reducing SiO2 is an exothermic reaction, during the high-temperature experiment, as the temperature rises, the steel near the inclusion particles begins to melt first, but at this time the contact area between the molten steel and the inclusions is small, which leads to a relatively small calculated diffusion coefficient of SiO2 in the inclusion particles. Therefore, this experimental method is not suitable for studying the mass transfer coefficient of the exothermic reaction between molten steel and inclusion particles.
[0086] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A new method for measuring the diffusion coefficient of a substance in inclusions in steel, characterized in that: The following steps are involved: Acquiring experimental materials and pre-treating the experimental materials; wherein the experimental materials include steel samples and inclusions; The high-temperature modification experiment was carried out on the pre-treated experimental materials through high-temperature confocal equipment, and the inclusion composition at different times was analyzed according to the experimental data; The initial conditions of the kinetic model are obtained, and the mass transfer coefficient of inclusions is estimated based on the initial conditions and inclusion composition analysis.
2. The new method for measuring the diffusion coefficient of a substance in steel inclusions according to claim 1 is characterized in that: The process of pre-treating the steel sample comprises: After cutting the steel sample into several cylinders of the same preset size, the steel sample is cold mounted using UV glue; the prepared steel sample is polished and cleaned step by step; after polishing, it is placed in a container filled with alcohol for ultrasonic cleaning.
3. The new method for measuring the diffusion coefficient of a substance in inclusions in steel according to claim 2, characterized in that: The preset dimensions include height and diameter, with the height ranging from 3-5 mm and the diameter ranging from 5-10 mm.
4. The new method for measuring the diffusion coefficient of a substance in inclusions in steel according to claim 1, characterized in that: The process of pre-treating the inclusions includes: Slag containing the ingredients required for the experiment is obtained and ground and mixed to obtain powdered preheated slag; the powdered preheated slag is pressed into round cakes of a preset size, the round cakes are heated to prepare pre-melted slag, the pre-melted slag is crushed and selected, and inclusion particles that meet size conditions are screened out; wherein the preset size conditions include the size and the error of each group of inclusion particles, the size is 100-300μm, and the error between the sizes of each group of inclusion particles does not exceed 40μm.
5. The new method for measuring the diffusion coefficient of a substance in steel inclusions according to claim 4 is characterized in that: When the temperature is raised to prepare the pre-melted slag, the insulation temperature needs to be controlled to be 50-100°C higher than the complete melting temperature of the slag, and the insulation time needs to be controlled to be 20-30 minutes.
6. The new method for measuring the diffusion coefficient of a substance in steel inclusions according to claim 1 is characterized in that: The high-temperature modification experiment is carried out on the pre-treated experimental materials by high-temperature confocal equipment. The process of analyzing the inclusion composition at different times according to the experimental data includes: The reaction time corresponding to each group of inclusion particles is obtained through preliminary experiments, and a high-temperature modification experiment is carried out on the pretreated experimental material based on the reaction time; when the reaction time is reached, helium is filled into the heating furnace for cooling; the experimental material after the experiment is taken out, and the composition of the inclusion particles is analyzed using a scanning electron microscope to obtain the inclusion composition; wherein the cooling rate is controlled at 300-1000°C.
7. The new method for measuring the diffusion coefficient of a substance in steel inclusions according to claim 1 is characterized in that: The initial conditions of the kinetic model include the density and volume of the inclusion particles; the density of the inclusion particles is calculated based on the relationship between the molar volume of the oxide and the temperature with the following formula: r liquidslag =∑x MO ·r MO ; In the formula, ρ liquidslag is the density of liquid slag, kg·m -3 ;x MO is the mass percentage of different oxides in the slag, wt%; ρ MO is the density of different oxides in the slag, kg·m -3 ;M MO is the molar mass of different oxides in the slag, kg·mol -1 ; Z MO is the molar volume of different oxides in the slag, m 3 ·mol -1 .
8. The new method for measuring the diffusion coefficient of a substance in inclusions in steel according to claim 1, characterized in that: The volume calculation formula of inclusion particles is as follows: V is the volume of the liquid inclusion particle, m -3 ; R is the radius of the liquid inclusion particles after being flattened on the surface of the steel sample, m; θ is the contact angle between the liquid inclusion particles and the solid steel.
Citation Information
Patent Citations
Method for researching reaction between molten steel and foreign non-metallic inclusions
CN116499824A
Prediction and verification method of calcium modified alumina inclusion
CN117347359A
Method for estimating diameter of inclusion in steel
JP2008128863A
Method for inspecting aluminum-based inclusion in high-strength steel by ultrasonic axial loading fatigue testing
JP2012073059A